Do soaring global oil prices heat up the housing market? Evidence from Malaysia - Thai-Ha Le (Economics: The Open-Access, Open-Assessment E-Journal, 2015)
This study analyses the effects of oil price and macroeconomic shocks on the Malaysian housing market using a SVAR framework. The specification of the baseline model is based on standard economic theory. The Gregory-Hansen (GH) cointegration test reveals that there is no cointegration among the variables of interest. The results obtained from the Toda-Yamamoto (TY) non-Granger causality test show that oil price, labor force and inflation are the leading factors responsible for changes in the Malaysian housing prices. The findings from estimating generalized impulse response functions (IRFs) and variance decompositions (VDCs) indicate that oil price and labor force shocks are responsible for substantial fluctuations in the price of housing in Malaysia.
Keywords: Q43; O18; F62; 330; housing market fluctuations; oil price shocks; macroeconomic shocks; Malaysia